2022
DOI: 10.1038/s41598-022-21405-y
|View full text |Cite
|
Sign up to set email alerts
|

First serological evidence of Q fever in large ruminants and its associated risk factors in Punjab, Pakistan

Abstract: Coxiellosis, also known as Q fever, is a zoonotic disease caused by Coxiella burnetii, a gram-negative bacterium that exerts a significant deleterious impact on the productive and reproductive capabilities of livestock, severely effecting the economics of this sector. In this study, 448 sera samples from cattle (n = 224) and buffalo (n = 224) were collected from 112 farms in Pakistan and examined for antibodies against C. burnetii using an indirect ELISA. Ticks were also collected from these animals. Serologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 82 publications
2
3
0
Order By: Relevance
“…It is noteworthy that a prior investigation revealed that the age group of animals between 1 and 2 years old saw the greatest impact following the introduction of Q fever into the herd [ 19 ]. Additionally, a study conducted in 2017 found that the prevalence of Q fever infection in Saanen goat kids was reduced at 6 months of age compared to one-year-old goats, which aligns with the findings of the current study [ 13 ]. However, a prior investigation demonstrated that the majority of Saanen goat kids, previously identified as lacking antibodies, would develop antibodies as they grew older, even in the absence of adult goats.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is noteworthy that a prior investigation revealed that the age group of animals between 1 and 2 years old saw the greatest impact following the introduction of Q fever into the herd [ 19 ]. Additionally, a study conducted in 2017 found that the prevalence of Q fever infection in Saanen goat kids was reduced at 6 months of age compared to one-year-old goats, which aligns with the findings of the current study [ 13 ]. However, a prior investigation demonstrated that the majority of Saanen goat kids, previously identified as lacking antibodies, would develop antibodies as they grew older, even in the absence of adult goats.…”
Section: Discussionsupporting
confidence: 90%
“…The occurrence of these diseases often led to financial losses due to sickness, decreased ability to reproduce, and reduced overall output [ 11 , 12 ]. Regarding goats especially, clinical symptoms of Q fever infection include events such as abortions, stillbirths, and the birth of weak offspring [ 13 , 14 ]. The investigation found that 70% of goats in the Besut District were observed to have Q fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in the United States, Hungary, and the Czech Republic, higher prevalences were reported, with 90.0, 97.2, and 91.6% of herds being positive, respectively [23,49,50]. In Denmark, Iran, Pakistan, and Belgium, prevalences similar to ours were observed, with 59.0, 56.8, 58.9 and 57.9% of herds being positive [27,[51][52][53]. However, comparisons between studies using different methodologies, including different samples (blood or milk), criteria (individual or herd level), and diagnostic tests (ELISA, IFA, or PCR), are difficult to interpret [54], which highlights the importance of conducting new research to update information regarding this disease.…”
Section: Discussionsupporting
confidence: 70%
“…Coxiella burnetii is an obligate intracellular bacterium and the agent of Q fever in humans; Q fever is a zoonotic disease widely prevalent worldwide (except for New Zealand), characterized by high infectivity and long-term environmental persistence (Long et al 2019 ; Klemmer et al 2018 ). Ticks were not considered vectors of C. burnetii previously (Abdelkadir et al 2019 ), but the results of a recent study support the link between ticks and Q fever, with the latter 3× more likely to occur where the former is found (Hussain et al 2022 ). Ticks play an important role in the wild and peridomestic cycles of C. burnetii worldwide, having been isolated from at least 40 tick species within the Ixodidae and 14 tick species of the Argasidae (Bolaños-Rivero et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%